2017
DOI: 10.1590/0034-737x201764040009
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of castor bean hybrids under different plant densities

Abstract: RESUMOCastor bean grown at high plant densities can increase yield due to increased light interception and reduction in sink demand. The objective of this study was to evaluate the effect of plant density on growth of castor bean hybrids. The experiment was conducted in Botucatu, SP, Brazil, in a split plot randomized block design, with four replications, in 2011 and 2012. The main plot consisted of the sampling times and the subplots consisted of a 3x3 factorial, with the 3 genotypes in the first factor and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This crop is highly efficient in adjusting its morphology according to the plant density variations without compromising seed yield (Severino et al., 2017). For example, it has been reported that dense plant populations (>70,000 plants ha −1 ) increase leaf area index (LAI), which can lead to plant etiolation and alter biomass partitioning; even so, castor can ensure or also improve seed yield (Jeong et al., 2019; Pivetta et al., 2017; Severino et al., 2017; Soratto et al., 2011; 2012; Souza‐Schlick et al., 2014). The ability of castor plant to compensate wide plant arrangements or gaps to achieve high seed yield decreases under conditions of drought and low temperature, especially when these conditions occur between the vegetative and the beginning of reproductive phases (Pivetta et al., 2017; Severino et al., 2017; Soratto et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This crop is highly efficient in adjusting its morphology according to the plant density variations without compromising seed yield (Severino et al., 2017). For example, it has been reported that dense plant populations (>70,000 plants ha −1 ) increase leaf area index (LAI), which can lead to plant etiolation and alter biomass partitioning; even so, castor can ensure or also improve seed yield (Jeong et al., 2019; Pivetta et al., 2017; Severino et al., 2017; Soratto et al., 2011; 2012; Souza‐Schlick et al., 2014). The ability of castor plant to compensate wide plant arrangements or gaps to achieve high seed yield decreases under conditions of drought and low temperature, especially when these conditions occur between the vegetative and the beginning of reproductive phases (Pivetta et al., 2017; Severino et al., 2017; Soratto et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that dense plant populations (>70,000 plants ha −1 ) increase leaf area index (LAI), which can lead to plant etiolation and alter biomass partitioning; even so, castor can ensure or also improve seed yield (Jeong et al., 2019; Pivetta et al., 2017; Severino et al., 2017; Soratto et al., 2011; 2012; Souza‐Schlick et al., 2014). The ability of castor plant to compensate wide plant arrangements or gaps to achieve high seed yield decreases under conditions of drought and low temperature, especially when these conditions occur between the vegetative and the beginning of reproductive phases (Pivetta et al., 2017; Severino et al., 2017; Soratto et al., 2012). The seed yield is compromised under such conditions because plant biomass accumulated at the beginning of reproductive phase is the most important factor to determine castor seed production (Severino et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low plant height is important for R. communis to determine plant density, which may contribute to the adaptability of plants to different environments for single or intercropped cultivation (LISBOA et al, 2018;SORATTO et al, 2011). The development of castor bean plants with low heights may allow their growth in denser systems, which provides better area use, generating a higher production, and higher yields, since plants grown under denser systems present better light interception and significant decreases in vegetative drains (PIVETTA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One example is Brazil, where the policies have been intensively supporting the increase of the liquid biofuels production. As a result, the castor bean production is becoming steady and ever improved even where it was not traditionally grown [16][17][18]. Through governmental policies, the global market for Ricinus products has achieved 1378000 tonnes by the year 2014 culminating in 1777000 tonnes by 2016 [17] and is still projected to increase more by the years to come.…”
Section: Introductionmentioning
confidence: 99%